PENGARUH KUALITAS PELAYANAN DAN BAURAN PEMASARAN TERHADAP KEPUASAN PASIEN RUMAH SAKIT - Rifai, Mohammad Irham; Susanto, Susanto (Universitas Ahmad Dahlan, 2016)
Background: Hospitals play an importan role in the development of public health since it handling of public health. In general, patient expected a product or service can be accepted and enjoyed with good service. There are various factors that can affect patient satisfaction. Suspected factor in this study are service quality and marketing mix. Method: This study used quantitatif correlation study approach. It took place at Wirosaban General Public Hospital Yogyakarta City. Sample of this study were 100 patients. Data analysis used descriptive analysis, multiple linear regression analysis, t-test, F-test, and coefficient determination. Results: The result of this study indicated that service quality effect toward patient satisfaction, with t-value 5.543 and sig 0.000. The result of this study indicated that marketing mix effect toward patient satisfaction, with t-value 2.957 and sig 0.004. The result of this study indicate that service quality and marketing mix effect toward patient satisfaction simultaneously, with F-value 42.490 and sig 0.000. The coefficient of determination was 0.467 or 46.7%. This imply that 46.7% of patient satisfaction is explained by the variable service quality and the marketing mix. Conclusion: Quality of service and marketing mix effect on patient satisfaction either partially or simultaneously.